2021
DOI: 10.1021/acsaem.1c01573
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sodium Metal/Electrolyte Interface by a Localized High-Concentration Electrolyte for Sodium Metal Batteries: First-Principles Calculations and Experimental Studies

Abstract: The applications of Na metal batteries (SMBs) are restricted owing to the capacity attenuation and safety hazards during the cycling process, while a rational design of the electrolyte is critical on solving this problem. In this work, an electrolyte is designed by adding 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropylether (TTE) into a 3.8 M sodium bis­(fluorosulfonyl)­imide/1,2-dimethoxyethane (NaFSI/DME) electrolyte, forming the localized high-concentration electrolyte (LHCE) for constructing a stable so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…MD results from Piao et al suggest four and five FSI – -coordinated Li + ions accounted for a larger percentage in the diluent-added electrolyte (T3) compared to the original HCEs (D1, D4, and D7) (Figure e) . A lower degree of Na + solvation by DME solvents in the LCE than the HCE was also reported by Wang et al, which leads to more FSI – anions but fewer DME molecules decomposing on Na metal anodes . The above examples demonstrate the wide applicability of LHCEs in various rechargeable batteries.…”
Section: Electrolyte Microstructuressupporting
confidence: 60%
“…MD results from Piao et al suggest four and five FSI – -coordinated Li + ions accounted for a larger percentage in the diluent-added electrolyte (T3) compared to the original HCEs (D1, D4, and D7) (Figure e) . A lower degree of Na + solvation by DME solvents in the LCE than the HCE was also reported by Wang et al, which leads to more FSI – anions but fewer DME molecules decomposing on Na metal anodes . The above examples demonstrate the wide applicability of LHCEs in various rechargeable batteries.…”
Section: Electrolyte Microstructuressupporting
confidence: 60%
“…179 Additionally, Xiang et al reported that a NaF-rich SEI was formed on the Na anode surface when TTE was added into 3.8 M NaFSI/DME electrolyte to form an LHCE, as the formed Na + -1DME-2FSI − solvation structure led to the decomposition of more FSI − with less DME decomposition, enabling a high capacity retention of 98.4% after 1046 cycles at 2C in a Na||Na 3 V 2 (PO 4 ) 3 (NVP) cell (Figure 11i). 180 Moreover, Guo et al found that a robust and flexible organic−inorganic SEI layer can be formed in the electrolyte with the low LUMO energy (i.e., 1.0 M KFSI/EC + DEC), where the EC/DEC mixed solvents and FSI are more easily decomposed, enabling fast K + ion diffusion/desolvation for better potassium metal protection and cycling stability (Figure 11j). 166 However, these studies partially emphasize that the good stability of the solvation-structure-derived SEI contributes to the high metal anode performance but fail to take the interfacial behavior of the solvation structure into consideration, which can rationally illustrate the different performances observed in different electrolytes, as interpreted by Ming et al earlier in this section.…”
mentioning
confidence: 99%
“…Copyright 2020 Wiley-VCH. Reprinted with permission from ref . Copyright 2021 American Chemical Society.…”
mentioning
confidence: 99%
“…After 90s of Ar + sputtering, the F 1s peak of electrolyte salt/NaPF y /Na x PF y O z completely disappears, but the F 1s peak of NaF can still be observed (Figure b, Supporting Information), further proving that NaF accumulates gradually inside the SEI layer and contributes to its stability and Na + permeability. [ 36 ] The above results clearly show that the practical capacity of nanosized Na 2 C 6 O 6 is close to its theoretical capacity, which means that ≈2 extra Na + are being accommodated into the Na 2 C 6 O 6 in the range of 0.5–1.5 V. The exploration of its energy storage mechanism has not been performed between 0.5 and 1.5 V, so the related ex‐situ XRD patterns were shown in Figures a,b during the first cycle at various potentials versus Na/Na + . The open‐circuit voltage of the pristine nanosized Na 2 C 6 O 6 electrode is ≈2.5 V (stage i).…”
Section: Resultsmentioning
confidence: 99%